Sacred trust and sustainable future: embedding tawhidic epistemology values in waqf enterprises - Mhd. Sarif, Suhaimi; Hidayatullah, Rakhmad Agung; Firmansah, Yayan; Abdul Razak, Dzuljastri (MMU Press, 2026)
This study investigates the sustainability of waqf-based enterprises through the lens of tawhidic epistemology, positioning waqf not merely as a philanthropic mechanism but also as a divinely inspired economic model grounded in ubudiyyah (servitude to Allah), adl (justice), and intergenerational equity. The primary objective is to identify the underlying drivers that enable waqf enterprises to sustain their operations while fulfilling their Shari’ah-compliant fiduciary and social mission. Adopting a qualitative methodology, this research draws on in-depth semi-structured interviews with 15 waqf managers from various Malaysian states, selected for their leadership roles in managing active waqf entities across diverse institutional settings. Thematic analysis revealed five interdependent sustainability drivers: (1) value-based leadership rooted in taqwa (Godconsciousness), (2) collaborative governance that balances Shari’ah and operational needs, (3) stakeholder trust and engagement, (4) adaptive innovation responsive to contemporary challenges, and (5) mission-centricity anchored in amanah (ethical stewardship). These findings contribute to both theoretical and practical discourse by proposing a spiritually anchored sustainability model for waqf enterprises.